Regulatory Vacuum in Indonesian Law on AI Model Training: Legal Responsibility for Copyright Infringement in Kadrey Vs. Meta - Rheyna Reva Rachman; Aurora Jillena Meliala (PDIH Untag Semarang, 2025)
The development of artificial intelligence (AI), particularly big data-based generative models, has created new challenges in copyright protection. This research examines the regulatory gap in Indonesian law regarding the use of copyrighted works as training data in AI model training, focusing on normative analysis and a case study of Kadrey Vs. Meta Platforms Inc. The research method used in this article is normative law, conducted by examining the legal norms contained in laws and regulations. The results of this study demonstrate that the widespread use of unauthorized creative works has the potential to violate the economic and moral rights of creators, while also opening up debate regarding the application of the principle of fair use in the context of modern AI. In Indonesia, the unclear definition of creator, the status of AI-generated works, and the lack of regulations regarding dataset transparency and permission mechanisms exacerbate the existing legal vacuum. This research concludes that Indonesia needs comprehensive legal reform to regulate the use of copyrighted works in AI training. Thus, regulatory updates are urgently needed to ensure that technological advancements do not diminish legal protection for creators and the national intellectual property ecosystem.